GUILLAIN-BARRÉ SYNDROME ASSOCIATED WITH SARS-COV-2 INFECTION, CASE REPORT - Spindola, Gabriela; Moreira Rivelli, Álvaro; Aparecida Gonçalves dos Santos, Raphaela; Fernandes Moreira, Sheila; Salvador Pereira, Allan (Health and Society, 2021)
Considered a respiratory infection, COVID-19 can lead to neurological pathologies, including encephalitis, stroke, acute disseminated encephalomyelitis and peripheral neuropathies, such as Guillain-Barré syndrome. Guillain-Barré syndrome, also known as acute polyradiculoneuropathy, is an autoimmune disease of the nervous system. Its main manifestation is the acute inflammation of the nerves and nerve roots, attacking the myelin sheath. Bearing in mind the relationship between neurological disorders and COVID-19, the doctor can adopt the best approach for each case, knowing that the neurological manifestations of COVID-19 are varied and that the data on them continue to evolve as the pandemic progresses.